2005
DOI: 10.3386/w11032
|View full text |Cite
|
Sign up to set email alerts
|

Allander Series: Skill Policies for Scotland

Abstract: This paper argues that skill formation is a life-cycle process and develops the implications of this insight for Scottish social policy. Families are major producers of skills, and a successful policy needs to promote effective families and to supplement failing ones. We present evidence that early disadvantages produce severe later disadvantages that are hard to remedy. We also show that cognitive ability is not the only determinant of education, labor market outcomes and pathological behavior like crime. Abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…17 Supplementary variables include parental education and income levels, the age of the mother at birth, whether the respondent lived with both parents, and the respondent's marital status. These are considered to be important predictors of skill formation and labor market outcomes (Heckman & Carneiro, 2003;Heckman & Masterov, 2004;Stratton, 1993). Parental education is measured as the average of parents' years of education and parental income is a 2-year average measured in the first 2 years of the survey.…”
Section: Datamentioning
confidence: 99%
“…17 Supplementary variables include parental education and income levels, the age of the mother at birth, whether the respondent lived with both parents, and the respondent's marital status. These are considered to be important predictors of skill formation and labor market outcomes (Heckman & Carneiro, 2003;Heckman & Masterov, 2004;Stratton, 1993). Parental education is measured as the average of parents' years of education and parental income is a 2-year average measured in the first 2 years of the survey.…”
Section: Datamentioning
confidence: 99%
“…Speaking in financial terms, the Agenda and other non-governmental programs (such as NIFTeY) addressed the early years as actual investments and returns in specific dollar amounts (see e.g. US longitudinal studies by Heckman & Masterov, 2004). Return was calculated in the form of savings on welfare spending (Commonwealth of Australia, 2007, 10), such as crime, unemployment, social and health services and so on.…”
Section: Shifting Biopolitical Reasoning: Genealogy Of Human Capital mentioning
confidence: 99%
“…It is widely shown that children brought up in less favorable conditions obtain less education, despite the large financial returns to schooling (Heckman and Masterov (2005). Indeed there is a large correlation between the education level of parents and their children (Björklund and Salvanes (2011).…”
Section: Previous Literaturementioning
confidence: 99%